Overweight and obesity knowledge prior to pregnancy: a survey study - Nitert Marloes; Foxcroft Katie F; Lust Karin; Fagermo Narelle; Lawlor Debbie A; O'Callaghan Michael; Mcintyre H David; Callaway Leonie K (BMC, 2011)
Abstract Background Overweight and obesity are associated with increased risk for pregnancy complications. Knowledge about increased risks in overweight and obese women could contribute to successful prevention strategies and the aim of this study is to assess current levels of knowledge in a pregnant population. Methods Cross sectional survey of 412 consecutive unselected women in early pregnancy in Brisbane, Australia: 255 public women attending their first antenatal clinic visit and 157 women at private maternal fetal medicine clinics undergoing a routine ultrasound evaluation prior to 20 weeks gestation. The cohort was stratified according to pre pregnancy BMI (< 25.0 or ≥ 25.0). The main outcome measure was knowledge regarding the risks of overweight and obesity in pregnancy. Results Over 75% of respondents identified that obese women have an increased risk of overall complications, including gestational diabetes and hypertensive disorders of pregnancy compared to women of normal weight. More than 60% of women asserted that obesity would increase the risk of caesarean section and less than half identified an increased risk of adverse neonatal outcomes. Women were less likely to know about neonatal complications (19.7% did not know about the effect of obesity on these) than maternal complications (7.4%). Knowledge was similar amongst women recruited at the public hospital and those recruited whilst attending for an ultrasound scan at a private clinic. For most areas they were also similar between women of lower and higher BMI, but women with BMI < 25.0 were less likely to know that obesity was associated with increased rate of Caesarean section than those with higher BMI (16.8% versus 4.5%, P < 0.001). Higher educational status was associated with more knowledge of the risks of overweight and obesity in pregnancy. Conclusions Many women correctly identify that overweight and obesity increases the overall risk of complications of pregnancy and childbirth. The increased risks of maternal complications associated with being obese are better known than the increased risk of neonatal complications. Maternal education status is a main determinant of the extent of knowledge and this should be considered when designing education campaigns.